Submandibular thyroid (Journal of Institute of Medicine Nepal, 2011)
Submandibular thyroid is one of the rare locations of ectopic thyroid tissue. Only few cases have been reported in the literature. We report a case of 16 year old female patient presenting with ectopic submandibular thyroid tissue. Diagnosis was based on ultrasound and cytology. Keywords: Nepal; submandibular ectopic thyroid DOI: http://dx.doi.org/10.3126/joim.v32i2.4948 Journal of Institute of Medicine, August, 2010; 32: 53-55